The Effect of Female Education and Female Labor Force Participation Rate on Poverty Alleviation in East Java - Elisyabella, Thineza Vira (Journal of Development Economic and Social Studies, 2025)
This study aims to determine the effect of women's education and women's labor force participation rate on poverty alleviation in East Java. This research method uses quantitative methods analyzed using panel data regression analysis. Poverty in East Java is still above the national average from 2010 to 2022. In 2023, East Java's poverty rate was the highest after Yogyakarta Province. Efforts are needed to improve the quality of human resources through education. Individuals who have good formal education tend to have better access to stable jobs and better wages, which can help them avoid falling into poverty. The findings of this Random Effect Model estimation study show that partially women's education has a significant negative effect on poverty alleviation and women's labor force participation rate (TPAK) has a significant positive effect on poverty alleviation in East Java. Simultaneously, female education and female labor force participation rate have a significant effect on poverty alleviation in East Java.